A new species of Fizesereneia Takeda & Tamura, 1980 (Crustacea: Decapoda: Brachyura: Cryptochiridae) from Japan - Zayasu, Yuna; Nomura, Keiichi; Seno, Koutaro; Asakura, Akira (Zootaxa, 2013)
A new species of pit crab of the genus Fizesereneia Takeda & Tamura, 1980, Fizesereneia daidai sp. nov., is described and illustrated based on specimens collected from the scleractinian corals Micromussa amakusensis and Micromussa sp. in Japan. The new species, the sixth assigned to the genus, can be separated from its congeners by having an orange pos-terior carapace in life, a subrectangular carapace, the width to length ratio of the carapace depressions being approximately three-halves, the midline of the carapace depression being almost invisible in lateral view, and the ocular peduncles being mostly exposed. The usefulness of the fusion or separation of the pterygostomial region to the carapace as a generic char-acter is discussed.